2010
DOI: 10.1186/1750-1326-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants are a rational complementary therapy for the treatment of Alzheimer's disease

Abstract: There is a high prevalence rate (30-50%) of Alzheimer's disease (AD) and depression comorbidity. Depression can be a risk factor for the development of AD or it can be developed secondary to the neurodegenerative process. There are numerous documented diagnosis and treatment challenges for the patients who suffer comorbidity between these two diseases. Meta analysis studies have provided evidence for the safety and efficacy of antidepressants in treatment of depression in AD patients. Preclinical and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 227 publications
(237 reference statements)
2
56
0
1
Order By: Relevance
“…Two aMCI subjects received cholinesterase inhibitors (AChE-I), one received selective serotonin reuptake inhibitors (SSRI) and three received both medications as combination therapy. To control for effects of medication, which might improve memory performance (e.g., Aboukhatwa, Dosanjh, & Luo, 2010), analyses of all behavioral recognition parameter and ERP data were repeated excluding medicated aMCIs. These analyses revealed similar results as for the entire aMCI sample.…”
Section: Participantsmentioning
confidence: 99%
“…Two aMCI subjects received cholinesterase inhibitors (AChE-I), one received selective serotonin reuptake inhibitors (SSRI) and three received both medications as combination therapy. To control for effects of medication, which might improve memory performance (e.g., Aboukhatwa, Dosanjh, & Luo, 2010), analyses of all behavioral recognition parameter and ERP data were repeated excluding medicated aMCIs. These analyses revealed similar results as for the entire aMCI sample.…”
Section: Participantsmentioning
confidence: 99%
“…Recent efforts by Testa and co-workers [156] as well as Sterling and coworkers [45] resulted in the development of dual MAO and ChE inhibitors. Similarly, recent studies have also shown that adding anti-depressants to a therapeutic regimen resulted in reducing AD progression and improving emotional well-being [156,157].…”
Section: Mao Maois and Anti-depressantsmentioning
confidence: 98%
“…Providing the large overlap between AD and VaD in clinical symptomatology, pathophysiology and neurochemical mechanisms [60][61][62][63], an effective treatment for AD may also offer benefits as a symptomatic treatment in VaD. Although most of the effects of antidepressants have been ascribed to their functions of neurogenesis activity, neurotrophin modulation and reduction of proteotoxicity [64][65][66][67], it is possible that acting on HCN channels may also contribute to or be responsible for antidepressants' efficacy on dementia since there is an interaction between the serotonergic systems and HCN channels [68][69][70] and SSRI antidepressants inhibit 5-HT reuptake that can regulate the properties and trafficking of HCN channels via a way of activating PLC-PKA and p38-MAPK signaling pathways (Figure 2) [54,[71][72][73]. It is worth mentioning that we have recently observed that fluoxetine can ameliorate cognitive impairments induced by CCH via down-regulation of HCN2 surface expression in the hippocampal CA1 area in rats (The data have not been published) and data from others also have showed that SB202190, a p38-MAPK inhibitor, can significantly reduce neuronal apoptosis in the hippocampus and rescue spatial learning and memory deficits in a rat model of vascular dementia [74].…”
Section: Reviewmentioning
confidence: 99%